The relationship between life satisfaction, self-esteem, fear of missing out (FOMO), and social media addiction among university students in Malaysia - Che Amat, Muhammad Asyraf; Tugiman, Nurhanisah; Asri, Alia Sarah (South East Asia Association for Institutional Research, 2024)
The regular use of social media carries both benefits and harmful effects on individuals, especially the youth. Post-COVID-19, the use of the Internet and social media has become the new norm to build a social network, find information more conveniently, or simply stay updated with recent events and information. This study was conducted to identify the relationship between life satisfaction, self-esteem, Fear of Missing Out, and social media addiction among university students in Malaysia. This quantitative study was conducted at five research universities in Malaysia. Four instruments were used, namely the Satisfaction with Life, Rosenberg Self-Esteem Scale, Fear of Missing Out Scale and Social Media Addiction Scale-Student Form. The research data were analyzed based on descriptive and inferential statistics. The sampling used in this research was stratified random sampling and simple random sampling. Based on the results, this study found a significant relationship between all the independent variables in this study with social media addiction. The findings can be used as a guide for authorities at university or interested parties, and it is suggested that further studies can be carried out so that the issue of social media addiction can be examined and discussed more comprehensively.